Evaluation of the preliminary auditory profile test battery in an international multi-centre study. (May 2013) - van Esch, Thamar E. M.; Kollmeier, Birger; Vormann, Matthias; Lyzenga, Johannes; Houtgast, Tammo; Hällgren, Mathias; Larsby, Birgitta; Athalye, Sheetal P.; Lutman, Mark E.; Dreschler, Wouter A.
Abstract Objective: This paper describes the composition and international multi-centre evaluation of a battery of tests termed the preliminary auditory profile. It includes measures of loudness perception, listening effort, speech perception, spectral and temporal resolution, spatial hearing, self-reported disability and handicap, and cognition. Clinical applicability and comparability across different centres are investigated. Design: Headphone tests were conducted in five centres divided over four countries. Effects of test-retest, ear, and centre were investigated. Results for normally-hearing (NH) and hearing-impaired (HI) listeners are presented. Study sample: Thirty NH listeners aged 19–39 years, and 72 HI listeners aged 22–91 years with a broad range of hearing losses were included. Results: Test-retest reliability was generally good and there were very few right/left ear effects. Results of all tests were comparable across centres for NH listeners after baseline correction to account for necessary differences between test materials. For HI listeners, results were comparable across centres for the language-independent tests. Conclusions: The auditory profile forms a clinical test battery that is applicable in four different languages. Even after baseline correction, differences between test materials have to be taken into account when interpreting results of language-dependent tests in HI listeners.